(untitled) (Research, Society and Development, 2020)
Anemias are considered to be multifactorial conditions, of diverse origins and associated with different risk groups, being defined as a reduction in hemoglobin in erythrocyte cells. The present research aimed to establish the epidemiological and laboratory profile of anemic patients in a University Hospital. This is a quantitative, descriptive, cross-sectional and retrospective study. The analysis of blood counts dispatched in 2018 from patients with anemia was performed from a sample calculated with a 95% confidence level and a sampling error of 5%. Age-related data were collected; sex; self-declared color; naturalness; municipality of residence; patient’s situation, whether inpatient or outpatient and; hemoglobin measurement, corpuscular constants, presence of petylocytes and leukocyte and platelet count. Anemias were morphologically classified and stratified according to severity. The chi-square test was applied with the aid of the Statistics Package for the Social Sciences (SPSS) software, version 17.0, with a significance of 5%. The survey has an ethical appraisal certificate No. 01812918.3.0000.5214. The study confirms the importance of the theme “anemia” and presents new data in the context of Piauí. It portrays the low resolution of health services in the interior of the state and corroborates the clinical importance of blood count and good practices in hematoscopy.